Analysis of traces of prints and the effects of wind on bones of a modern vertebrate: contribution of taphonomy to the forensic registry (2019)
Introduction: Taphonomic analysis of bone remains could allow us to obtain information on some of thepost-depositional processes that affected them in the short, medium and long term. This work aims to expose some of the results on the formation and distribution of prints on bone remains as part of the diagenetic processes. Methods and materials: For the print analysis, five samples of flat bones, analyzed by means of the electron scanning electron microscopy technique, were selected. To obtain topographic images of the prints, a 3D optical profilometer was used. Results and discussion: Whilst pressing the periosteum surface onto the sediment, ablations (continuity solutions due to collapse of the periosteum) occur that are frequently associated with the presence of multiple prints. With respect to the marks produced by wind erosion, these show two types of morphology: one is presented as small holes with symmetrical perimeters, generally coinciding with the morphology of sediment grains. The other type of print shows a more asymmetrical shape in the form of an elongated shape. Conclusion: The taphonomic processes can be reconstructed from a diachronic sequence of the alteration that allows modeling a timeline that reconstructs the processes that affected the organic remains since the death of an organism. The diagenetic model of Equus sp. shows that wind erosion could remain within a few weeks of deposition and would act over longer periods of time, with an interruption period at the time of burial of Equus via sedimentation processes.